Factors Influencing Perceptions of Sport Coach Performance: A Scoping Review - Yusup, Novandi Firdaus; Prabowo, Trisnar Adi; Azhari, Haeruddin; Ari, M. Azy’ (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to identify and map the factors that influence the perception of sports coach performance based on published research results. The research design used is a scoping review, which allows researchers to explore key concepts and existing empirical evidence, while identifying gaps in the literature. The literature was obtained through a systematic search in the PubMed, Scopus, ProQuest, and Google Scholar databases, with keywords such as "coach performance", "perception", "sports coach", and "factors influencing". The articles analyzed were limited to publications in 2020–2024, in English, open access and were scientific articles. The results of this study found 8 articles, showing that the perception of coach performance is influenced by various factors such as leadership style, technical competence, coach personality, quality of coach-athlete relationship, communication strategy, and collaboration with the performance support team. A transformative and communicative leadership style, positive interpersonal relationships, and proper training planning have been shown to increase athletes' positive perceptions of coaches. These findings emphasize the importance of a holistic approach to evaluating coach performance, which includes technical, social, and emotional skills. This research is expected to be the basis for developing more effective sports coaches that are oriented towards the welfare and performance of athletes.